Glacier changes and associated climate drivers for the last three decades, Nanda Devi region, Central Himalaya, India. (20th February 2021) - Kumar, Vinit; Shukla, Tanuj; Mehta, Manish; Dobhal, D.P.; Singh Bisht, Mahendra Pratap; Nautiyal, Srikrishna
Abstract: The glaciers are considered as iconic indicators of climate change, and receding at differential rates worldwide. Variable retreat rates of glacier termini and inadequate supporting field data (e.g. mass balance, ice thickness, velocity, etc.) of the glaciers makes it difficult to access the impact of climate change. Here, we examined eight glaciers in the upper Rishi Ganga catchment, Nanda Devi region, Central Himalaya, India, to assess their spatial and temporal variability towards the climate change. The temporal coverage of analysis spans from twentieth to early twenty-first centuries (ranges 1980 to 2017). The study was designed by comparing the estimates of different temporal satellite images of the Hexagon KH-9 (1980) with Landsat 5 TM (1989), Landsat 7 ETM+ (1999), Landsat 8 OLI/TRIS (2017) and ASTER DEM (2011) with local and regional meteorological conditions of the study area. The upper Rishi Ganga catchment covers an area of ~690 km 2, having a glaciated area of ~243 km 2 (~35% of the total area) during 1980. Our study reveals that the glaciers of the valley lost ~26 km 2 (10%) of the glaciated area between 1980 and 2017. The total glacierized area in 2017 is ~217 km 2, which is ~26% of the total area. However, during the same periods (1980–2017) the Equilibrium Line Altitude (ELA) of the glaciers fluctuated between 5200 and 5700 m asl. The present study suggests that the glaciers in the region have responded to deprived precipitation conditions since 1980, overlapping our understanding of glacier retreat due to temperature increase, in the context of the global warming scenario.